Implementasi Widuri Sebagai Media Penyimpanan Laporan Dari Referensi Digital Karya Ilmiah - Untung Rahardja; Meta Amalya Dewi; Winiarti Prastiwi (CCIT Journal, 2014)
Reports of KKP / TA / SKRIPSI is one of the requirements that must be traveled by students to complete the final level of research that has been done. Preparation of reports are currently running manually using paper media . There were identified 5 ( five) subject matter that is formulated to find out the answer. There are also 3 ( three ) benefits , and there are 6 (six) advantages and 1 (one ) shortcomings of the proposed new system. Widuri is a medium for learning, especially Pribadi Raharja in Perguruan Tinggi Raharja. In order to enrich the insights and knowledge, sharing knowledge with others , improve and develop creativity in writing the article. To identify existing problems such as reports on library storage inefficient and writing reports that still use manual design methods ekplotatory author. The author also makes the UML and Literature review on Wiki as a research method. This study aims to allow students to use as a storage facility Widuri report of KKP / TA / SKRIPSI and make references that can be accessed online . By applying widuri as storag Report KPP / TA / SKRIPSI may facilitate students in making a report and look for references. It can be concluded that the WIduri is able to overcome the problems that occur in the collection of the report KKP / TA / SKRIPSI in Perguruan Tinggi Raharja.